2019
DOI: 10.1186/s12866-019-1590-8
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli O157:H7: distribution, molecular characterization, antimicrobial resistance patterns and source of contamination of sheep and goat carcasses at an export abattoir, Mojdo, Ethiopia

Abstract: Background Cattle have been identified as a major reservoir of E. coli O157:H7 for human infection; the ecology of the organism in sheep and goats is less understood. This study was carried out to determine prevalence, source of infection, antibiotic resistance and molecular characterization of Escherichia coli O157: H7 isolated from sheep and goat. Methods Systematic random sampling was carried out at Modjo export abattoir, Ethiopia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 42 publications
6
9
4
Order By: Relevance
“…Most the E. coli O157:H7 strains, however, produce stx2, although either stx1, or stx2, or both are produced (20). The results of this study showed that the percentage of the stx2 gene 44.4% is higher than the ratio of the stx1gene 33.3% of all isolates for dogs with and without diarrhea, This results disagree with study in Iran by Torkan et al (21) which appeared the stx1 gene 64.3% was higher than stx2 gene 35.7% in E. coli O157H:7 isolates from feces of dogs suffering from diarrhea (21).while our results were agreement with study on sheep by Abreham et al (22) showed the percentage of the stx2 gene 57.1% higher than stx1 gene 14.2% (22).…”
Section: Discussioncontrasting
confidence: 88%
“…Most the E. coli O157:H7 strains, however, produce stx2, although either stx1, or stx2, or both are produced (20). The results of this study showed that the percentage of the stx2 gene 44.4% is higher than the ratio of the stx1gene 33.3% of all isolates for dogs with and without diarrhea, This results disagree with study in Iran by Torkan et al (21) which appeared the stx1 gene 64.3% was higher than stx2 gene 35.7% in E. coli O157H:7 isolates from feces of dogs suffering from diarrhea (21).while our results were agreement with study on sheep by Abreham et al (22) showed the percentage of the stx2 gene 57.1% higher than stx1 gene 14.2% (22).…”
Section: Discussioncontrasting
confidence: 88%
“…Regarding the prevalence of E. coli O157: H7 in association with risk factors such as age, sex and body condition scores, during the present study it was found that there was significant variation among different slaughtered cattle age groups (young 16.7%, adult 7.4% and old 8.7%) of the study cattle with respect to the prevalence of E. coli O157: H7 (p<0.05). This finding is inline with the findings of Abreham et al 28 who reported the prevalence of E. coli O157: H7 can significantly vary in relation to the age of the cattle. However, the finding by Mekonnen et al 35 showed insignificant statistical difference (p> 0.05) between the age groups regarding the prevalence of E. coli O157: H7 which contradicts the present finding which could be related to the underdeveloped immune status of young cattle.…”
Section: Discussionsupporting
confidence: 92%
“…This considerable variation could be attributed to the prolonged storage of the isolated E. coli samples with glycerol suspension at low temperature. The sample type based prevalence of E. coli O157: H7 from feaces also is in agreement with the findings from these studies 28 , 29 from Hawassa and Canada respectively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Escherichia coli O157:H7 is one of the most ubiquitous foodborne zoonotic pathogens [1][2][3]. Sewage irrigation and manure application to soil have caused the pathogen to seep into soil matrices [4].…”
Section: Introductionmentioning
confidence: 99%